Standard Protocol for Exchange of Health-checkup Data Based on SGML: The Health-checkup Data Markup Language (HDML) - Sugimori, H.; Yoshida, K.; Hara, S.; Furumi, K.; Tofukuji, I.; Kubodera, T.; Yoda, T.; Kawai, M. (Methods of Information in Medicine, 2002)
Objectives: To develop a health/medical data interchange model for efficient electronic exchange of data among health-checkup facilities.Results: A Health-checkup Data Markup Language (HDML) was developed on the basis of the Standard Generalized Markup Language (SGML), and a feasibility study carried out, involving data exchange between two health checkup facilities. The structure of HDML is described.Results: The transfer of numerical lab data, summary findings and health status assessment was successful.Conclusions: HDML is an improvement to laboratory data exchange. Further work has to address the exchange of qualitative and textual data.
Keywords: Database; data linkage; computer communication networks; electronic data processing